A CDMA interference canceling receiver with an adaptive blind array. - Ghazi-Moghadam, V. (IEEE Journal on selected areas in communications)
Interference cancelling receivers have been suggested as low complexity multiuser receivers for code division multiple access (CDMA) systems. A multi-element interference cancelling receiver is proposed, and it is demonstrated that using spatial information about the users will improve the performance of the receiver. Two blind algorithms are suggested to adaptively combine the outputs of the antenna elements. The performances of these algorithms are compared, and it is shown that without requiring any additional information, the receiver can spatially discriminate between the users and improve the error performance